Analisis Rantai Pasok Madu di CV. Madu Apriari Mutiara, Kecamatan Cimanggis, Kota Depok, Jawa Barat: Analysis of the Honey Supply Chain at CV. Madu Apriari Mutiara, Cimanggis Sub-district, Depok City, West Java - Sebayang, Veralianta Br; Putri, Annisa Oktaviana; Prameswara, Dhita Icha; Farizan, Fajrina Nur; Najmaayyubi, Fathiya; Nainggolan, Kristina Leonita; Malleon, Saddam Cahya; Angelita, Tasya (Journal of Integrated Agribusiness, 2024)
The supply chain is a series of business processes connecting various entities to enhance product value and deliver it to consumers. This research aims to describe and analyze the honey supply chain at CV. Madu Apriari Mutiara, a small-to-medium enterprise based in Cimanggis, Depok, West Java. The study employs both descriptive qualitative and quantitative methods, utilizing primary data gathered through surveys and interviews, and secondary data from relevant literature. Findings reveal two main marketing channels: direct-to-consumer sales and sales via retailers. CV. Madu Apriari Mutiara encounters challenges related to significant price fluctuations, with the highest marketing margins observed in longer supply chains (Rp165,000-Rp175,000) and higher farmer share values in shorter channels (36%-42%). To improve supply chain efficiency, it is recommended to diversify marketing channels through e-commerce, adopt technology-driven supply chain management, and enhance marketing strategies. Furthermore, partnerships with farmers should be reinforced through training programs and stable price guarantees.